1999
DOI: 10.1074/jbc.274.36.25317
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Dodecasaccharide Binding to Platelet Factor-4 and Growth-related Protein-α

Abstract: ␣-Chemokines are known heparin-binding proteins. Here, a heparin dodecasaccharide (H12) was purified and used in NMR studies to investigate binding to growth-related protein-␣ (Gro-␣) and to platelet factor-4-M2 (PF4-M2), an N-terminal chimera of PF4. Pulsed field gradient NMR was used to derive diffusion coefficients as the protein (monomer):H12 ratio was varied. In the absence of H12, both PF4-M2 and Gro-␣ give diffusion coefficients consistent with the presence of mostly dimers. As the PF4-M2:H12 ratio is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
28
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 55 publications
4
28
0
1
Order By: Relevance
“…The monosaccharides are sulfated to various extents and linked via 1f 4 glycosidic bonds. [21][22][23] Most common to porcine mucosal heparins (75%) are disaccharide repeats of 2-Osulfated-iduronic acid and 6-O-sulfated, N-sulfated-glucosamine. 23 The influence of heparin on protein aggregation is complicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The monosaccharides are sulfated to various extents and linked via 1f 4 glycosidic bonds. [21][22][23] Most common to porcine mucosal heparins (75%) are disaccharide repeats of 2-Osulfated-iduronic acid and 6-O-sulfated, N-sulfated-glucosamine. 23 The influence of heparin on protein aggregation is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the present study was to investigate this last form of aggregation, the so-called "isoelectric precipitation" of insulin 19 at low I and the effect on it of heparin, a highly charged biopolymer whose biological functions are intimately connected with its ability to bind biofunctionally numerous proteins. 20,21 A member of the glycosaminoglycan family, heparin is composed of variable disaccharide units of uronic acid and glucosamine. The monosaccharides are sulfated to various extents and linked via 1f 4 glycosidic bonds.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, IL8 has been shown to function both as a monomer and dimer (17). In its well known capacity to bind heparin, PF4 functions optimally as a tetramer in vitro (18,19) and presumably as a tetramer in vivo due both to the presence of heparan sulfate normally found on the surface of cells and because it is released from ␣-granules of platelets in relatively large quantities upon tissue injury.Previous studies (20,21) have shown that mixing various chemokines in solution can significantly modify their biological activities, but no thorough explanation as to why this occurs has been given. Here we use NMR spectroscopy and computational modeling to demonstrate that when present together in solution, CXC chemokines PF4 and IL8 interact with each other and exchange subunits to form AB-type heterodimers.…”
mentioning
confidence: 99%
“…In vitro, IL8 has been shown to function both as a monomer and dimer (17). In its well known capacity to bind heparin, PF4 functions optimally as a tetramer in vitro (18,19) and presumably as a tetramer in vivo due both to the presence of heparan sulfate normally found on the surface of cells and because it is released from ␣-granules of platelets in relatively large quantities upon tissue injury.…”
mentioning
confidence: 99%
“…Several of the biological activities of proteoglycans are attributable to the GAGs. For example, heparin binds anti-thrombin III (1), and heparin and HS bind fibroblast growth factor (2) and various chemokines (3)(4)(5). Furthermore, CS binds a subset of chemokines, such as RANTES (regulated on activation normal T cell expressed and secreted) (6) and PF-4 (platelet factor-4) (7).…”
mentioning
confidence: 99%